Comprehensive Management of Water Resources: A Step-By-Step Path Towards a Sustainable Campus At The U.D.C.A (Bogotá, Colombia) - Camilo A. Peraza (Journal of Sustainability Perspectives, 2024)
Universities are recognized as essential agent of change since future decision-makers related to sustainability are going and will pass through their classrooms. This circumstance becomes an excellent opportunity to demonstrate, with example, and instill in the students how these types of organizations control and approach implementing practices that guarantee sustainability and the appropriate use of resources over time. The Universidad de Ciencias Aplicadas y Ambientales has undertaken different actions related to the Integrated Water Resources Management (IWRM) on campus since 1990. This work focuses on the actions carried out by the Integrated Environmental Management System (latest institutional management model) between the 2014-2016 period to improve the university campus's IWRM (drinking water and wastewater management) from a systemic point of view. The actions implemented were part of the project: Reusing treated water at the University's Wastewater Treatment Plant (WWTP). This project included the following objectives: 1) Reduce the volume and economic costs of sludge water disposal; 2) Reduce drinking water consumption; and 3) Promote environmental education about water resources in students of the different programs of the University. The results were: 1) A decrease of 68.3% in volume and 69.5% in costs of sludge water disposal; 2) A 41.2% saving in drinking water consumption; and 3) 2,475 members of the university community impacted by issues related to the management of water resources.